004 Validation of the diagnostic criteria for sporadic Creutzfeldt-Jakob disease. Issue 6 (27th May 2022) - Watson, Neil; Brandel, Jean-Philippe; Green, Alison; Hermann, Peter; Ladogana, Anna; chiari, Maurizio Poc-; Smith, Colin; Summers, David; Zerr, Inga; Pal, Suvankar
Abstract : Sporadic Creutzfeldt-Jakob disease (sCJD) is the commonest form of CJD, a universally fatal and rapidly progressive human prion disease. sCJD typically presents with rapidly progressive dementia but can have diverse manifestations. The diagnosis can be challenging. Diagnostic criteria were revised in 2017 to include the real-time quaking-induced conversion (RT-QuIC) assay and cortical ribboning on magnetic resonance imaging (MRI). The aim of this study is to validate the diagnostic criteria, with the secondary aim of evaluating its impact on classification during life and hence case ascertainment. 501 deceased subjects with post-mortem (PM)-confirmed sCJD between 2017–2019 were included from the national registries of the UK, France, Germany and Italy. A control group of 146 subjects with alternative diagnoses at PM was included. Diagnostic test outcomes were recorded. RT-QuIC was 91.6% sensitive and 100% specific. MRI was the second most sensitive (86.8%) and specific (91.9%) investigation. Codon 129 had a significant impact on MRI changes in sCJD (p<0.001). Subjects were classified during life according to the previous and updated criteria to assess the impact on ascertainment. Revised criteria increased in-life sCJD diagnosis rates by 22.4%. In conclusion, the diagnostic criteria are highly sensitive and specific, allowing effective differentiation of sCJD from potentially treatable mimics, and enhancing in-life sCJD diagnosis. neil: watson@nhslothian.scot.nhs.uk 27